Factors Associated with Adolescent Premarital Sex at SMA Negeri 1 Lembo, North Konawe Regency - Wa Ode Hardian; Sartiah Yusran; I Made Christian Binekada (Formosa Journal of Sustainable Research, 2023)
Premarital sex among adolescents is increasing rapidly and has become a health problem in the world, especially in Indonesia. Purpose: The purpose of this study was to find out what causes are associated with adolescent premarital sex behavior at SMA Negeri 1 Lembo, North Konawe Regency. Methods: This study is a quantitative study with a cross-sectional design. the sample in this study were 176 respondents using probability sampling and analyzed using multivariate analysis. Results: The results showed that the influence of family roles on premarital sex behavior was 0.018 and that of peers was 0.000. Conclusion: It can be concluded that for the role of family (parents) and peers have an effect on the incidence of premarital sex among adolescents in SMA Negeri 1 Lembo